THE IMPACT OF A NEW PEDAGOGICAL INTERVENTION ON NURSING STUDENTS' KNOWLEDGE ACQUISITION ON SIMULATION-BASED LEARNING - BASHIR , S; YASMEEN , S; NAWAZ , R; NAZAR , K (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the impact of a new pedagogical intervention on nursing student's knowledge acquisition in simulation-based learning. Quasi-experimental study. This study was conducted at the College of Nursing, Holy Family Hospital Rawalpindi. One hundred nursing students from 3rd year were selected for the study who volunteered for participation. Participants were divided into 2 equal groups, with 50 participants in each group through computer-generated randomization. In Group A, students were given the new pedagogical intervention of simulation-based learning, while Group B was the control group where the existing study program was continued. A pretest comprised of 15 questions was conducted before the study from the participants of both groups. These questions covered pathophysiology, symptoms, and nursing actions. The study's primary outcome was set as the differences in knowledge among nursing students of Group A and Group B assessed through post-test scores. All the participants were female nursing students with a Mean ± SD of 20.1±0.83 years. Knowledge acquisition was significantly better in Group A compared to Group B (Post-test score: 9.86±1.63 vs.. 8.48±1.61 respectively, p-value=0.000). Students' perception score was also significantly higher in Group A than in Group B (8.34±0.87 vs.. 7.52±0.83, p-value=0.000). The Simulation-based learning intervention results in a significant improvement in the learning capability and knowledge of nursing students. Therefore, SB learning in the nursing curriculum is suggested to improve theoretical and practical knowledge acquisition.